2012
DOI: 10.1111/j.1600-0587.2012.07738.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐generational long‐distance migration of insects: studying the painted lady butterfly in the Western Palaearctic

Abstract: Jason W. 2013 Multi-generational longdistance migration of insects: studying the painted lady butterfly in the Western Palaearctic. Ecography, 36 (4). 474-486. 10.1111/j.1600-0587.2012.07738.x Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. (up to 60 degrees of latitude). The cycle comprises an annual poleward advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
199
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(208 citation statements)
references
References 48 publications
6
199
1
2
Order By: Relevance
“…This means that summer breeding in Maghreb mountains is at most a local phenomenon and cannot explain the origin of most butterflies appearing south of the Sahara in autumn. Although migration between Europe and the African tropical savannah had already been suggested [6,7,15], our analyses represent the first empirical European butterflies comprised a mixture of early and late migratory waves, while Sahelian butterflies only corresponded to more recent waves. For a migratory insect, colonization of the Sahel and further south in autumn seems highly adaptive, as the whole region offers suitable breeding conditions coinciding with a short period of high productivity after the rainy season [7,17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that summer breeding in Maghreb mountains is at most a local phenomenon and cannot explain the origin of most butterflies appearing south of the Sahara in autumn. Although migration between Europe and the African tropical savannah had already been suggested [6,7,15], our analyses represent the first empirical European butterflies comprised a mixture of early and late migratory waves, while Sahelian butterflies only corresponded to more recent waves. For a migratory insect, colonization of the Sahel and further south in autumn seems highly adaptive, as the whole region offers suitable breeding conditions coinciding with a short period of high productivity after the rainy season [7,17].…”
Section: Resultsmentioning
confidence: 99%
“…Although its general pattern of migration is known, many uncertainties regarding the distances covered by individual butterflies and the movements within Africa still exist. First, it has never been shown that the butterflies appearing south of the Sahara in autumn (sometimes in great numbers) have a European origin [6,7]. Second, although it is believed that northwestern Africa (Maghreb) is colonized in autumn by European migrants, both ground-level and radar observations of northward migration in Morocco and Mauritania in October-November also point to sub-Saharan origins [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although miniaturization of tags will certainly extend the range of trackable insect taxa, some miniature insects are trackable only in groups, for instance, with help of citizen science [64] or various radar technologies [35,65,66] (table 2 and next section).…”
Section: (A) Tracking Individual Insectsmentioning
confidence: 99%
“…The Pleine-Fougè res study site is part of the ''Zone Atelier Armorique'' experimental site and belongs to a Long Term Ecological Research network (LTER S1001201). This site was chosen to study migration dynamics because it is located on migratory routes of many insect species (Chapman et al 2012, Stefanescu et al 2013, and because it is far enough away from southern Europe that variations in the dD ratio between local individuals and immigrants from the south can be detected.…”
Section: Insect Samplingmentioning
confidence: 99%